PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELI KONSUMEN EMKA GENTENG BETON DI CIANJUR - Alifia Nurul Aulia; Hendar Rubedo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the influence of product, promotion, price, and place on purchasing decisions at EMKA Genteng Cianjur. This study is a correlational study using a survey method with a questionnaire instrument. Based on the results of the study, the promotion coefficient r count = .768 with r table (0.05) (15) = 0.657. Thus, it can be concluded that the promotion variable has a significant influence of 51.6% on purchasing decisions at EMKA Genteng Cianjur. Based on the results of the study, the price coefficient r count = 0.768 > r table (0.05) (18) = 0.657. Thus, it is concluded that the price variable has a significant influence of 51.6% on purchasing decisions at EMKA Genteng Cianjur. Based on the results of the study, the purchasing decision coefficient r count = 0.768 > r table (0.05) (18) = 0.657. Thus, it is concluded that the place variable has a significant influence of 51.6% on purchasing decisions at EMKA Genteng Cianjur”, meaning the coefficient is significant. Thus, the hypothesis that states “promotion and price analysis have an influence on purchasing decisions” can be accepted.